A7 PI3KP110δ DRIVES INTESTINAL FIBROSIS IN SHIP DEFICIENT MICE. (1st March 2018) - Lo, Y; Sauvé, J; Menzies, S; Sly, L M
Abstract: Background: Crohn's disease (CD) is an immune-mediated disease characterized by inflammation along the gastrointestinal tract. One in 3 people with CD will develop intestinal fibrosis requiring surgery within 10 years of diagnosis. Despite dramatic improvements in reducing intestinal inflammation in people with CD, some still develop fibrosis and there are no treatments that target intestinal fibrosis directly. Our laboratory has reported that mice deficient in the Src homology 2 domain-containing inositolphosphate 5'-phosphatase (SHIP -/- ) develop spontaneous CD-like ileal inflammation with arginase-dependent fibrosis. We have also reported that high arginase activity in SHIP -/- cells is dependent on the p110δ catalytic subunit of class IA phosphatidylinositol 3-kinase (PI3K). Based on this, we hypothesize that SHIP -/- mice develop CD-like intestinal fibrosis due to increased PI3Kp110δ activity. Aims: Aim 1: To determine whether genetic inactivation of PI3Kp110δ activity prevents the development of ileal fibrosis in SHIP -/- mice Aim 2: To determine whether pharmacological inhibition of PI3Kp110δ activity can block or reverse ileal fibrosis in SHIP -/- mice Methods: SHIP -/- mice were crossed with mice deficient in PI3Kp110δ activity (PI3Kp110δ DA/DA ) to generate wild type, SHIP -/-, PI3Kp110δ DA/DA, and SHIP -/- PI3Kp110δ DA/DA mice. Mice were assessed for fibrosis and compared at 4, 8, and 12 weeks of age. SHIP -/- mice (8-week-old) were treated with the PI3Kp110δ isoform-specific inhibitor, IC87114 (or vehicle), for two weeks. Ileal fibrosis was assessed in 8-week-old SHIP -/- mice and compared to mice treated with inhibitor or vehicle. Measurements of ileal fibrosis include muscle thickening, accumulation of vimentin + mesenchymal cells, collagen accumulation by Masson's trichrome staining and Sircol assay, arginase activity, and TGFβ, IL-4, and IL-13. Results: SHIP -/- PI3Kp110δ DA/DA mice have less ileal fibrosis than their SHIP -/- littermates including reduced muscle thickening, vimentin + mesenchymal cells, collagen accumulation, arginase activity, TGFβ, IL-4, and IL-13. Pharmacological inhibition of PI3Kp110δ activity in SHIP -/- mice also reduced the above parameters. Intriguingly, PI3Kp110δ deficiency or inhibition reduced ileal inflammation in SHIP -/- mice including immune cell infiltration and IL-1β production, suggesting that PI3Kp110δ and/or fibrosis, itself, may contribute to inflammation. Conclusions: PI3Kp110δ activity drives ileal fibrosis in SHIP -/- mice. Moreover, targeting PI3Kp110δ activity effectively reverses SHIP -/- ileal fibrosis. Importantly, people with CD have reduced SHIP activity and so fibrosis, in people with CD, may be amenable to treatment by inhibiting PI3Kp110δ activity. Idelalisib, a PI3Kp110δ inhibitor, is already licensed for use in people with certain leukemias and lymphomas, so may be rapidly translatable into effective therapy for intestinal fibrosis in people with CD. Funding Agencies: CCC, CIHR